Management challenges in delivering an international sport and development program. Issue 3 (13th July 2015) - MacIntosh, Eric; Couture, A. Lauren; Spence, Kirsty
Abstract : Purpose: – The primary purpose of this paper is to explore stakeholder perceptions of an international sport for development program so as to identify some of the management challenges within a strategic management framework. The secondary purpose is to provide recommendations for the focal organization's leadership based on those stakeholder perceptions. Hence, participants in this study directly experienced the facilitation and implementation of the international sport for development program. Participant viewpoints are expressed in efforts to identify improvement opportunities in the delivery and operations of this sport for development program. Design/methodology/approach: – In this qualitative research, a case study design was chosen to produce a detailed account of the Commonwealth Games Association of Canada's (CGC) International Sport and Development (IDS) program. Interviews were conducted with 24 alumni of the IDS program, five CGC IDS administrators, and ten host IDS organization administrators from African and Caribbean regions. Findings: – Findings demonstrated shared perspectives regarding the challenges and various management practices among the three stakeholder groups investigated. In particular, funding and human resource stress was found to be the largest obstacles of maintaining programming and achieving desired outcomes. Several strengths and limitations in the program design, monitoring and evaluation strategy, and program documentation of outcomes were found which can presumably be used to help formulate management strategy moving forward in efforts for continuous improvement. Research limitations/implications: – The study does not take into account the stakeholder group of participants whom were deemed to be on the receiving end of the program and not responsible for the delivery and operations of the initiatives which were the focus of the study. Practical implications: – Recommendations in lieu of present challenges and objectives are also offered and are based on information from the facilitators and implementers of the principal program of research and the results of the semi-structured interviews. Originality/value: – This study examines three different stakeholders that are responsible for the facilitation and implementation of the design, delivery, and daily operations of sport for development projects within an international partnership context.